Intrahousehold resource allocation in developing countries: models, methods, and policies - Haddad, Lawrence James; Hoddinott, John F.; Alderman, Harold (International Food Policy Research Institute, 1997)
In this book economists, demographers, sociologists, and anthropologists collaborate in the study of how resources are allocated within households in developing countries and why it matters from a policy perspective. Surveying a broad body of theory and evidence, the contributors examine the many social and cultural factors that influence decisions at the family and household level about the allocation of time, income, assets, and other resources. Shedding new light on a process that is often hidden from view and difficult to measure, they show that a more complete understanding of intrahousehold behavior can increase the likelihood that policies will reach the people they are intended to affect--leading to better policies in areas such as food production and consumption, nutrition, natural resource management, and fertility.